Additional Use of Alarm Systems in Wakefulness in the Treatment of Mono-Symptomatic Nocturnal Enuresis - Kosilov, Kirill Vladimirovich; Loparev, Sergey Alexandrovich; Kuzina, Irina Gennadyevna; Shakirova, Olga Victorovna; Zhuravskaya, Natalia Serveevna; Lobodenko, Alexandra (Journal of Nepal Paediatric Society, 2016)
Introduction: There are many factors associated with nocturnal enuresis in children and can be very challenging as regards its management. Consequently, misunderstanding could arise explaining the state when a child for years urinates in bed. The aim of this study was to investigate possibilities of increase of efficiency of alarm systems and decrease of time of result achievement in case of usage of such modernized therapy algorithm. Materials and methods: 452 children (307 boys and 145 girls) took part in the study. All patients were randomly divided into two groups prior to alarm systems therapy. Group А patients (206) were offered to use alarm system (Wet Stop/ BYE-WET by PALCO LABS, Inc (USA) in normal mode. Group В patients (246) were using alarm system in wakefulness – urinated on device catching sensor. Alarm intervention was carried out within 12 weeks, total period of observation over the patients– 5 months. Results: We found out that number of patients with urination in sleep after 3 months of therapy was reliably less in this group than in control (23.5 against 40.3 percent, p < 0.05). Conclusion: Usage of alarm systems in patient’s wakefulness in addition to standard treatment regimen was improved the efficiency of Alarm-therapy up to 76.5 percent. Day training with the usage of alarm systems reliably increased the number of dry nights and self-wakening in case of desire to urinate. Usage of alarm systems in wakefulness was safe and did not result in additional refusal from treatment. J Nepal Paediatr Soc 2016;36(1):8-13